Overview of Hepatitis C Elimination Efforts in Pakistan and the Launch of Prime Minister’s Programme for the Elimination of Hepatitis C - Huma Qureshi; Saeed Akhter; Hassan Mahmood; Saeed Hamid; Ammara Naveed; Aamir Ghafoor Khan; Shabana Saleem; Mariyam Sarfraz; Atiya Aabroo; Ambreen Arif (Journal of the Pakistan Medical Association, 2024)
Hepatitis B and C are serious viral infections that cancause liver damage and death. According to the WorldHealth Organization (WHO), there are currently 2.8 millionpeople living with hepatitis B in Pakistan, and 9.8 millionpeople living with hepatitis C.1 These numbers representa significant burden of disease for the country. Thecurrent prevalence of hepatitis B in Pakistan is 1.1%,which corresponds to one-quarter of the burden of thedisease in the Eastern Mediterranean region.1 Theprevalence of hepatitis C is 7.5%, which is the highest inthe world. Almost 37,000 people die each year in Pakistandue to hepatitis B and C.2 The high prevalence of hepatitisB and C in Pakistan is a major public health concern. Theseinfections can lead to serious health complications,including liver cancer and cirrhosis. The economic cost ofhepatitis in Pakistan is also significant, due to lostproductivity and healthcare expenses. Continued...